Understanding of Real Estate investment Risk and Opportunity (Study Business and Economic Management) - Widjaja, Gunawan; Ekasari, Silvia; Sijabat, Hotmaria Hertawaty; Nurwita, Nurwita; Hendriarto, Prasetyono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Understanding the risks and opportunities in real estate investing is an exciting study for academic purposes and business applications in the field. The author believes that this question is very relevant to be discussed to understand the opportunities and risks if someone wants to run a property business, which is a very lucrative business opportunity. To complete the discussion of this theme, we have conducted a series of electronic data searches on several publication databases, journals, books, and websites that actively discuss the risks and opportunities of investing in real estate, both nationally and internationally. We cannot describe the data validly and adequately if we do not do an in-depth study first, involving a data coding system and a thorough evaluation to get data findings that can answer. We carried out data published in the last ten years from 2010 to 2021, considering that today's data is so fast that it continues to change and evolve. Based on the phenomenological study we saw from the extensive data exploration. We found several points which in general were understanding the opportunities of the risk of investing in property, so based on this discussion, we can conclude that the opportunity is this considering that property is a business that never runs out and cannot be as easy as others are in motion and the sale and purchase, they only need to maintain, and the risk will usually occur if mismanagement and natural disasters such as floods and fires, the rest of the property business opportunities are indeed very promising. Thus, this finding should be a complement to the same studies.